Physiotherapy performance in patients with obstetrical brachial palsy: a literature review (Research, Society and Development, 2022)
Introduction: This study discusses the role of physiotherapy in the treatment of obstetric brachial palsy, including physiotherapeutic exercises as a complementary treatment that provides a better quality of life for these patients. Objective: to determine, through a systematic review, which physical therapy exercises are effective in the treatment of obstetric brachial palsy. Methodology: This is a review study. Studies originally published in Portuguese and English, published between 2010 and 2021, were analyzed using the following databases: Medical Literature Analysis and Retrieval System Online (MEDLINE) via PubMed, Latin American and Caribbean Literature in Health Sciences (LILACS), CAPES Periodicals and in the Scientific Electronic Library Online (SciELO) virtual library. Results: The results showed that physiotherapeutic treatment options are defined by clinical assessment and type of injury. Conclusion: It was considered that physiotherapeutic treatment should be started early for a faster and more effective recovery of functional capacity, which suggests further research, practical studies that address the theme of this subject.